2015
DOI: 10.1039/c5cc07765f
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a degradable polyanion for layer-by-layer assembly for encapsulation and release of cationic functional biomolecules

Abstract: A novel degradable polyanion, poly(phthalic ethylene glycol ester), was synthesized in one pot in a single step. The degradable polyanion assembles with various polycations to form layer-by-layer films that can encapsulate physiologically active biomolecules. Polyanion degradation can induce film disassembly and release of the encapsulated functional protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…They proved that the tuning of encapsulation conditions would affect the functions of platelets [17]. Surface characteristics of encapsulated cells, such as roughness and stickiness, were then investigated in a followed study [18]. Further, Diaspro et al found that proliferation of cells could be affected by coating with PAH and In 2000, Möhwald et al firstly introduced cell encapsulation via LbL.…”
Section: History Of Lbl Single-cell Encapsulationmentioning
confidence: 99%
“…They proved that the tuning of encapsulation conditions would affect the functions of platelets [17]. Surface characteristics of encapsulated cells, such as roughness and stickiness, were then investigated in a followed study [18]. Further, Diaspro et al found that proliferation of cells could be affected by coating with PAH and In 2000, Möhwald et al firstly introduced cell encapsulation via LbL.…”
Section: History Of Lbl Single-cell Encapsulationmentioning
confidence: 99%
“…A number of methods have been reported for chemically altering the surface properties of materials and functionalizing their surfaces. These include plasma treatment, self-assembled monolayer formation, vapor deposition, , layer-by-layer assembly, , Langmuir–Blodgett deposition, solution coating (painting), mussel-inspired adhesion, , and physical adsorption to material surfaces. Coating with a functional polymer solution is a versatile approach for functionalizing an inert material surface. , The major advantages of coating are that (i) it is a simple process often requiring no special apparatus, (ii) a wide variety of functional polymers are available, which can be chemically designed and tuned to demands, (iii) various substrates including organic and inorganic materials can be coated with a functional polymer, if the polymer is adhesive to the material surface, (iv) various coating techniques including dip-coating, brush coating, spray coating, spin-coating, and electrocoating are available according to practical demands, and (v) it minimizes the amount of coating material that is required and does not impair the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods have been reported for chemically altering the surface properties of materials and functionalizing their surfaces. These include plasma treatment, 1 self-assembled monolayer formation, 2 vapor deposition, 3,4 layer-by-layer assembly, 5,6 Langmuir−Blodgett deposition, 7 solution coating (painting), 8−11 mussel-inspired adhesion, 12,13 and physical adsorption to material surfaces. 14−16 Coating with a functional polymer solution is a versatile approach for functionalizing an inert material surface.…”
Section: ■ Introductionmentioning
confidence: 99%